2012
DOI: 10.1002/app.38630
|View full text |Cite
|
Sign up to set email alerts
|

13C‐NMR, 13C‐13C gCOSY, and ESI‐MS characterization of ether‐bridged condensation products in N,N′‐dimethylurea‐formaldehyde systems

Abstract: The reaction of urea with formaldehyde is the basis for the production of urea‐formaldehyde (UF) resins which are widely applied in the wood industry. The presence of ether‐bridged condensation products in the UF resin reaction system is an open question in the literature. It is addressed in the present work. The N,N′‐dimethylurea‐formaldehyde model system was studied since it is chemically similar to the UF resin reaction system but allows for a simple elucidation of all reaction products. It was analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Chemical shifts of the species identified in the reaction system 1,3-dimethylurea-formaldehyde, Part I (hydroxymethylation products). The chemical shifts of formaldehyde FA and the methyleneglycols MG 1:::10 can be found elsewhere [4,14,15] [23,24] Because of this evidence, the formation of ether bridges has been taken into account in the present study in the reaction kinetic model. More details on the indications supporting the formation of ether bridges as found during the course of the present work are provided in the Supplementary Information.…”
Section: Ether Bridgesmentioning
confidence: 96%
See 2 more Smart Citations
“…Chemical shifts of the species identified in the reaction system 1,3-dimethylurea-formaldehyde, Part I (hydroxymethylation products). The chemical shifts of formaldehyde FA and the methyleneglycols MG 1:::10 can be found elsewhere [4,14,15] [23,24] Because of this evidence, the formation of ether bridges has been taken into account in the present study in the reaction kinetic model. More details on the indications supporting the formation of ether bridges as found during the course of the present work are provided in the Supplementary Information.…”
Section: Ether Bridgesmentioning
confidence: 96%
“…The reaction kinetic constants k C 5:::14 of the forward reactions and the equilibrium constants K 5:::14 describing the formaldehyde-water section of the model were taken from the work of Hahnenstein. [15,36] For the hydration of formaldehyde, Hahnenstein used the empirical approach of Schecker and Schulz [37] to estimate k C 5 in dependence of temperature and pH value, as given by Eqn (23). The parameters C 3 , C 4 , C 5 , A 2 , and B 2 are listed in Table 6.…”
Section: Determination Of Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…After the acidic condensation, the pH is adjusted back to alkaline and the additional urea (the second urea) is added to lower the F/U molar ratio to 0.9-1.2, aiming to capture the un-reacted formaldehyde. Although intensive studies have been completed to investigate the chemical structures of resin polymers by employing nuclear magnetic resonance d(NMR) analysis [3][4][5][6][7][8][9][10][11][12][13][14][15], our survey of the literature showed that the effects of post-added urea on the UF polymers were not focused or well-discussed. However, this issue is important for better understanding the relationship between low molar ratio and poor performance of the resin.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra were recorded at 150 MHz with 400-600 scans accumulated. The observed chemical shifts were assigned by referring to the assignments in the literature [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Procedures For Quantitative 13 C-nmr Determinationmentioning
confidence: 99%